Cuts destroy, hurt, kill: a critical metaphor analysis of the response of UK academics to the UK overseas aid budget funding cuts. Issue 1 (2nd January 2022) - Imperiale, Maria Grazia; Phipps, Alison
ABSTRACT: In this article, we analyse the response of UK academics to the UK government decision to cut international development research funding as part of the overseas aid budget reduction, undertaken in March 2021. This decision affects and will have long-lasting effects on any research project involving the UK and international partners, particularly in Global South contexts. We use Critical Metaphor Analysis (CMA) to analyse news, blogs, interviews that UK-based academics wrote in response to the cuts announcement, from 11 March 2021 to 30 April 2021. We identified the following metaphors: CUTS ARE AN ENTITY; CUTS ARE A THREAT, CUTS ARE ILLNESS, CUTS ARE VIOLENCE; plus, on the other hand, RESEARCH IS HEALTH, RESEARCH IS A JOURNEY, RESEARCH IS CONNECTION. UK academics have used 'idioms of distress', which are cultural expressions, often metaphorical, through which people articulate distress. Therefore, our contribution is threefold. First, we suggest that the metaphors used have a persuasive and evaluative aim and function. Second, we open up a space for an interdisciplinarity between CMA and 'idioms of distress'. Third, we warn about the need for the UK government and responsible institutional bodies to restore communication and trust with the global academic research community in International Development.